2021
DOI: 10.1038/s41598-021-88415-0
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of disease onset, progression and sex differences from androgen receptor levels in a mouse model of amyotrophic lateral sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is an adult-onset neurodegenerative disorder caused by loss of motor neurons. ALS incidence is skewed towards males with typically earlier age of onset and limb site of onset. The androgen receptor (AR) is the major mediator of androgen effects in the body and is present extensively throughout the central nervous system, including motor neurons. Mutations in the AR gene lead to selective lower motor neuron degeneration in male spinal bulbar muscular atrophy (SBMA) patients, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 68 publications
0
1
0
Order By: Relevance
“…Accumulating evidences [ 29 33 ] demonstrated that female mice show less variability in the survival time than male mice, and the instability of the males' endocrine hormones would affect the experimental results [ 34 36 ]. Therefore consistent with previous reports, female mice were elected in this study.…”
Section: Methodsmentioning
confidence: 99%
“…Accumulating evidences [ 29 33 ] demonstrated that female mice show less variability in the survival time than male mice, and the instability of the males' endocrine hormones would affect the experimental results [ 34 36 ]. Therefore consistent with previous reports, female mice were elected in this study.…”
Section: Methodsmentioning
confidence: 99%